Analisis Banjir Akibat Sudetan Meandering Sungai Kolokoso Studi Kasus : Bandara Dhoho, Kediri - M Gilang Indra Mardika; Tera Melya Patrice Sihombing; Ryan Andreas (Jurnal Aplikasi Teknik Sipil, 2025)
The construction of Dhoho Kediri Airport has altered land use in the Kolokoso Watershed, increasing flood risks. To mitigate this, a cutoff channel was proposed for the meandering river section. Hydrological analysis utilized the Log Pearson III distribution and Mononobe method for a 25-year return period. Effective rainfall was derived via the Alternating Block Method, and peak flood discharge was calculated at 0.829 m³/s using the SCS Unit Hydrograph. HECRAS 6.4.1 simulations modeled the implementation of three box culverts (4.8 m x 4.3 m). Results indicate a significant reduction in flood inundation area from 5.93 ha to 0.65 ha. Validation demonstrated high model accuracy, showing 89% agreement for water levels and98% for flow velocities.